2009
DOI: 10.1074/jbc.m605716200
|View full text |Cite
|
Sign up to set email alerts
|

Bestrophin-1 Enables Ca2+-activated Cl− Conductance in Epithelia

Abstract: Epithelial cells express calcium-activated Cl؊ channels of unknown molecular identity. These Cl ؊ channels play a central role in diseases such as secretory diarrhea, polycystic kidney disease, and cystic fibrosis. -activated Cl Ϫ channels (CaCC) 2 are present in almost every cell type examined. Although this type of channel has been studied extensively, the molecular identity of CaCC in epithelial tissues remains a mystery (1, 2). The channels are of small conductance, show outward rectification upon moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…The putative role of bestrophin as the CaCC is questioned though by the observation that a large fraction of heterologous expressed bestrophin appears intracellularly [175,177,179]. This contradicts its function as a membrane channel.…”
Section: Bestrophins Are Strongly Associated With the Cgmp-dependent mentioning
confidence: 98%
See 3 more Smart Citations
“…The putative role of bestrophin as the CaCC is questioned though by the observation that a large fraction of heterologous expressed bestrophin appears intracellularly [175,177,179]. This contradicts its function as a membrane channel.…”
Section: Bestrophins Are Strongly Associated With the Cgmp-dependent mentioning
confidence: 98%
“…Several other groups have recently used siRNA technique in cell culture and found an association between the bestrophin proteins and I Cl(Ca) [179,181,185,195,196,197]. We have found that downregulation of bestrophin-3 in mesenteric small artery VSMCs with siRNA suppressed the cGMP-dependent I Cl(Ca) without affecting the co-expressed classical I Cl(Ca) [112].…”
Section: Bestrophins Are Strongly Associated With the Cgmp-dependent mentioning
confidence: 99%
See 2 more Smart Citations
“…While cAMP-dependent Cl Ϫ secretion by CFTR is well examined, detailed analysis of epithelial Ca 2ϩ -dependent Cl Ϫ secretion is hampered by the lack of a molecular counterpart. Although bestrophins may form Ca 2ϩ -dependent Cl Ϫ channels and facilitate Ca 2ϩ -dependent Cl Ϫ secretion in epithelial tissues (10,11), they are unlikely to form secretory Cl Ϫ channels in the apical cell membrane, because Ca 2ϩ -dependent Cl Ϫ secretion is still present in epithelia of mice lacking expression of bestrophin (12). Bestrophins may rather have an intracellular function by facilitating receptor mediated Ca 2ϩ signaling and activation of membrane localized channels (13).…”
mentioning
confidence: 99%